Implementation of restorative justice in criminal case settlement to overcome over capacity of correction institutions - Rinaldi, Ferdian (ARKA INSTITUTE, 2025)
This research addresses the use of the restorative justice concept to address issues of overcrowding in correctional facilities. The implementation of coaching inmates and correctional students via an educational, rehabilitation, and reintegration-based correctional system is a responsibility of correctional institutions. However, excessive tamping power might lead to other, more complicated issues, making the coaching development now being implemented suboptimally. A restorative justice strategy is one that may be better suited for addressing the overcrowding in correctional facilities. This research employs a normative juridical methodology. The study's findings demonstrate that Indonesian correctional facilities' overcrowding of inmates may be addressed by using the restorative justice idea. By putting this idea into practice, the usage of criminal penalties in relevant laws and regulations may be reduced, allowing criminals to avoid constantly being placed in community facilities. With a variety of legal analysis techniques, research on restorative justice may still advance, giving scholars a fantastic opportunity to expand on the practice's ideas. In particular, the ability of Indonesian scholars to provide fresh insights on the development of Indonesian law.